History Teachers' Efforts to Improve Learning Effectiveness by Optimizing Museums as Learning Resources - Dewi, Sri Utami; Marcelli, Fabio; Gibson, Melody Kay (Journal of Social Knowledge Education (JSKE), 2024)
Purpose of the study: The purpose of this study is to determine how to optimize the function of the museum as a source of history learning at State Islamic High School 1 Probolinggo. The main purpose of the study is to optimize the function of this museum to increase the effectiveness of history learning. By optimizing the function of this museum, students can be more effective in learning history. Methodology: This research on history teachers' efforts to improve learning effectiveness through optimizing the function of museums as learning resources at State Islamic High School 1 Probolinggo City is a qualitative descriptive research. A form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena. This research aims to obtain information and describe the results of the research. Main Findings: This study specifically explores the role of history teachers in local history learning at State Islamic High School 1 Probolinggo. The focus on the contribution of history teachers to students' understanding of local history shows the uniqueness of this study in discussing important aspects of history learning. This study provides valuable insights into the role of history teachers in the context of local history learning, with a focus on integration, local resources, and the development of students' historical awareness. Novelty/Originality of this study: this study not only identifies the role of museums as sources of historical learning, but also tries to measure and optimize its impact concretely in the context of historical learning at State Islamic High School 1 Probolinggo. This approach can provide a strong basis for further development in improving the effectiveness of historical learning in other schools.